UPGRADING OF HEAVY NAPHTHA TO GASOLINE-LIKE LIQUID USING Fe AND Zn SUPPORTED ZEOLITE CATALYSTS - FAKHRULDIN, AFEEFAH (2021)
ASEAN region is heavily dependent to fossil fuel for energy sources, contribute to the depletion of primary gasoline source. The conversion of crude oil distillate has been the imperishable objective in the refinery research agenda in finding the suitable catalyst formulation. Thus, this research work aims to develop Fe and Zn/zeolite supported catalyst for upgrading of heavy naphtha to higher octane gasoline-like liquid. In the extent to determine the catalyst performance and quality of the gasoline produced, various loading of Fe and Zn (1-5 wt.%) in respect to zeolite support catalysts were prepared using the incipient wet impregnation method. The catalysts were characterized for physicochemical properties and screened using fixed-bed continuous reactor equipped with GC-FID. The GC-FID comply with ASTM D6730-01 to determine hydrocarbon components which covered the yield and RON value of the gasoline produced. Furthermore, accomplishment of heavy naphtha upgrading not only measure by the yield and RON value but also the specification comparison with the current EURO 5 standard and the catalyst reusability. Results obtained show that 5 wt.% Zn/zeolite has successfully converted heavy naphtha to gasoline with highest yield at 68.69 wt.% and RON value of 103.1 at 450 °C, 14 bar and LHSV of 2 h-1 which supported by the catalyst highest acid density (2.61 μmol/m2). The specification of the produce gasoline is also comparable to the EURO 5 standard and the catalyst has a long shelf life up to 35 hours with a 0.0108 g coke deposited and 6% metal leaching.